Perancangan Performance Measuremen System (PMS) Perusahaan X di sentra Usaha Mikro Kecil dan Menengah (UMKM) Sepatu Cibaduyut - Yohanes Dicka Pratama; Paulus Sukapto; Carles Sitompul (Universitas Katolik Musi Charitas, 2017)
Micro Small and Medium Enterprises (MSMEs) have a very strategic role in a country. In addition to providing alternative employment, MSMEs also have good staying power in case of difficult economic emergencies. However, on the other hand there are many challenges that are heavy by businesses belonging to SMEs. Many of the same kind of businesses emerging are increasingly tighter. Performance Measurement System (PMS) is a control system of business conducted by the organization or company. With PMS the company can monitor effectively and efficiently the operational activities undertaken. However, not all performance measurement system frameworks can be implemented on a system, a UMKM. SMEs have different characteristics when compared with large businesses that have a better management system. Therefore, it is necessary to develop different approaches for designing performance measurement system applied to MSMEs. Company X is a company belonging to Micro Small and Medium Enterprises (MSMEs). Company X is in the center of footwear business Cibaduyut. Company X is a company engaged in the distribution of products produced by footwear pengerajin in the area Cibaduyut. The problem that Company X is experiencing is the ability to control and control the operational activities undertaken. The design of performance measurement system begins with indicators, key performance indicators (KPI). From this research is made 27 KPI.